Kemampuan Predasi Tungau Predator Amblyseius sp. Resisten Temperatur terhadap Tetranychus urticae - Budianto Heru Bambang; Edi Basuki (Universitas Lampung, 2013)
he predation ability of temperature resistant Amblyseius sp. to Tetranychus urticae. Global warming and climate changes have caused great mortality of the predatory mites Amblyseius sp. that disrupts the natural control of Tetranychus urticae. In contrast, the low humidity and high temperature led to an increase in the population of T. urticae. The purposes of this study were to determine the effect of temperature on population of the predatory mites Amblyseius sp. and to determine the predation ability of temperature resistant Amblyseius sp. on T. urticae. The selection of Amblyseius sp. was conducted at temperatures of 15, 20, 25, 30 and 35 0C. The parental predatory mite Amblyseius sp., and subsequent descendants were exposed to the temperature range until the values of the LT50 fiducial limits (FL) of a certain generation did not overlap with that of the previous one. The effectiveness of Amblyseius sp. predation ability was studied using an experimental method i.e. completely randomized design with four treatments and ten replications . For this purpose, each stage of T. urticae, i.e. egg, larvae, nymph and adult was set as treatment and was given to any type of temperature resistant predatory mite Amblyseius sp. The results showed that by using the temperature gradient, we managed to select temperature-resistant individuals from their population. These individuals formed a population that was resistant to temperature of up to 33.3oC without losing their predatory capacity, especially on the egg stage of T.urticae.